An equation is shown below:
(4x - 1) + (2x + 2) = 1
Which statement shows a correct next step in solving the equation? (1 point)
Question 18 options:
1) The equation can become 6x + 1 = 1 by combining like terms.
2) The equation can become 3x + 4x = 1 by solving the terms in the brackets.
3) The equation can become 3x + 4x = 1 by applying the associative property of multiplication.
4) The equation can become 6x + 1 = 1 by applying the distributive property.

See more answers at brainly.com

(4x - 1) + (2x + 2) = 1
4x - 1 + 2x + 2 = 1
add

6x +1 = 1

The equation can become 6x + 1 = 1 by applying the distributive property.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.